The relationship between CALLY index and stroke in hypertensive patients: insights from NHANES - Xingfu Fan; Di Qing; Jin Zhao; Yang Luo; Xiaofang Li; Wenqin Tan; Shiping Liu (Frontiers in Nutrition)
BackgroundAt present, stroke ranks as the third leading cause of mortality, and hypertension is a major risk factor for stroke. Complementary assessment of inflammation level, immunity, and nutritional status is now possible using the newly developed C-reactive protein-albumin-lymphocyte (CALLY) index biomarker. One key concern in this study is that its correlation with the risk of stroke in individuals with hypertensiveness.MethodsIn this study, we used cross-sectional analyses from the National Health and Nutrition Examination Survey (NHANES) database through 2003 to 2010. The CALLY index was calculated by albumin and lymphocytes divided by C-reactive protein (CRP). In order to further analysis, the CALLY index was log-transformed to increase data normality and lessen the impact of extreme values on the analytical findings. We investigated the odds ratios and confidence intervals of the ln CALLY index and its components in connection to stroke in people with hypertension. A weighted multivariable logistic regression model was carried out. Additionally, we used weighted restricted cubic splines (RCS) and subgroup analyses to further examine the association between the CALLY index and stroke prevalence in hypertensive individuals.ResultsThis study included 8,146 hypertensive participants, of whom 616 hypertensive participants had a stroke. In unadjusted modeling, we found a 39% reduction in the incidence of stroke in the hypertensive population in the highest ln CALLY quartile group (OR 0.61, 95% CI 0.46–0.82), and the negative association remained significant after adjustment for confounders. While ALB showed a robust protective impact in hypertensive people, with greater ALB levels linked to a decreased risk of stroke (OR 0.50, 95% CI 0.37–0.68), we also discovered a positive correlation between CRP and stroke risk (OR 1.13, 95% CI 1.04–1.22). A substantial correlation between the ln CALLY index and stroke risk in hypertensive individuals was also validated by subgroup analysis. The ln CALLY index and stroke risk in this sample also showed a strong linear negative connection, according to weighted restricted cubic spline (RCS) analysis.ConclusionThere is a significant negative association between the CALLY index and stroke risk in hypertensive patients in the U.S. adults. The CALLY index may be a potential indicator for early identification of individuals at higher risk of stroke in hypertensive patients and provide potential for clinical intervention.